BOPET base film for polarizing plate release film
Patent Information
- Application Number
- CN202611319808.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]目前现有技术中,常规双向拉伸聚酯基膜仍有缺陷,其抗静电性能和耐热老化性能难以适配复杂生产与使用环境,例如,显示器件生产车间多为高洁净、高精密工况,薄膜收卷、分切、贴合过程中易因摩擦产生静电,吸附空气中的微尘杂质,污染偏光片光学表面,引发显示黑点、瑕疵等质量问题
1、本发明通过引入含季铵盐阳离子基团的功能助剂,大幅提高了基膜的抗静电性能,有效防止因摩擦静电吸附微尘,避免偏光片光学表面污染及显示黑点等质量问题,并且相比传统的涂布工艺,简化了实验操作;
Smart Images

Figure REF-OBJ-1787898908350-000001 
Figure REF-OBJ-1787898908350-000002
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyester film technology, specifically, it relates to a BOPET base film for use as a release film for polarizers. Background Technology
[0002] With the rapid iteration of high-end electronic industries such as LCD, flexible display, and touch optics, polarizers, as the core optical components of display panels, directly determine the imaging quality and user experience of terminal display devices. Biaxially oriented polyester film (BOPET), with its excellent mechanical strength, light transmittance, dimensional stability, and chemical corrosion resistance, has become the mainstream base film material for mass production applications of polarizer release films, and is widely suitable for polarizer protection in various display terminals such as mobile phones, tablets, automotive displays, and LCD TVs.
[0003] Currently, conventional biaxially oriented polyester (BOPET) films still have shortcomings. Their antistatic and heat aging resistance properties are difficult to adapt to complex production and usage environments. For example, display device manufacturing workshops are often characterized by high cleanliness and high precision. During the film winding, slitting, and lamination processes, static electricity is easily generated due to friction, attracting airborne dust and impurities, contaminating the optical surface of the polarizer, and causing quality problems such as display black spots and defects. In addition, existing BOPET films are prone to slight dimensional deformation and transmittance reduction under heat aging conditions. After long-term use, this will indirectly affect the optical stability and lamination accuracy of the polarizer, making them unsuitable for the long-term use requirements of harsh environments such as automotive displays and outdoor commercial displays.
[0004] Therefore, it is urgent to solve the above problems and design a biaxially oriented polyester film that combines antistatic properties and heat aging resistance for use as a release film for polarizers. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a BOPET base film for polarizer release film.
[0006] The objective of this invention can be achieved through the following technical solutions: A BOPET base film for use as a release film for polarizers comprises the following raw materials in parts by weight: 70-80 parts PET chips, 8-15 parts functional additives, 0.3-0.6 parts composite antioxidants and 0.4-0.9 parts hydrolysis stabilizers.
[0007] Preferably, the functional additive is prepared by the following steps: S1. In a three-necked flask equipped with a mechanical stirrer and a reflux condenser, 4,4'-methylenediphenol, ethanolamine and toluene are added sequentially. Stirring is started and the mixture is heated to 80-85°C. Then, paraformaldehyde is added in 4-5 batches. After all the paraformaldehyde has been added, the temperature is raised to 110-115°C. The mixture is refluxed at this temperature for 4-5 hours. After the reaction is complete, the intermediate product A is obtained after post-processing. S2. In a four-necked flask equipped with a mechanical stirrer, a constant-pressure dropping funnel, and a reflux condenser, add intermediate product A and acetonitrile in sequence, start stirring, and place the flask in an ice-water bath (0-5℃) to cool. Using a constant-pressure dropping funnel, slowly add iodomethane dropwise into the flask. After the addition is complete, remove the ice-water bath and slowly heat the reaction system to 40-45℃. At this temperature, reflux the reaction for 6-8 hours. After the reaction is complete, after post-processing, intermediate product B is obtained. S3. In a four-necked flask equipped with a mechanical stirrer, reflux condenser, thermometer, and pressure reducing port, terephthalic acid, ethylene glycol, polyethylene glycol, intermediate product B, and antimony glycolate (catalyst) are added sequentially. The temperature is raised to 180-185℃, and the system pressure is maintained at -0.02MPa (slight negative pressure). The reaction is mechanically stirred for 3-4 hours to complete the esterification reaction. After esterification, nitrogen gas is slowly introduced into the flask to replace the air for 10-20 minutes. Then, the vacuum degree is increased (-0.098MPa), and the temperature is raised to 210-215℃. Under these conditions, the mixture is continuously stirred and polycondensed for 6-8 hours. After polycondensation is completed, the functional additive is obtained after post-processing.
[0008] Preferably, the ratio of 4,4'-methylenediphenol, ethanolamine and paraformaldehyde in step S1 is 20g:13.5-14.1g:12.6g.
[0009] Preferably, the ratio of intermediate product A to iodomethane in step S2 is 37.1g:15.8-16.2g.
[0010] Preferably, the ratio of terephthalic acid, ethylene glycol, polyethylene glycol and intermediate product B in step S3 is 83g:43.4g:35g:15.2-16.1g.
[0011] In the preparation of functional additives, the present invention requires control of the ratio of raw materials used in steps S1 and S2. For example, in step S1, the molar ratio of 4,4'-methylenediphenol and ethanolamine should be controlled to be close to 1:2, with the latter slightly in excess, to ensure complete reaction. Similarly, in step S2, the molar ratio of intermediate product A and iodomethane (volatile) should be controlled to be close to 1:2.5 to ensure complete reaction.
[0012] The reaction equations for steps S1 and S2 are as follows:
[0013] The functional additive prepared in this invention belongs to the polyether ester antistatic agent class. The structural fragments of this type of antistatic agent are similar to the chemical structure of the matrix resin, thus ensuring good interfacial compatibility between the functional additive and the matrix and guaranteeing the light transmittance of the base film. In addition, the functional additive molecule also contains quaternary ammonium salt cationic groups, which can coordinate with the ether oxygen bond to promote ion pair dissociation, increase the carrier concentration, and play a synergistic role. Moreover, after the introduction of quaternary ammonium salt, even in the dry polarizer production clean room (low humidity), static charge can be quickly leaked through ion conduction, effectively preventing the adsorption of micro dust. Finally, the benzoxazine ring contained in the functional additive molecule is a rigid six-membered heterocycle with an extremely high thermal decomposition temperature, which can significantly improve the heat aging resistance of the matrix.
[0014] Preferably, the composite antioxidant is a hindered phenolic antioxidant and a phosphite antioxidant, compounded in a mass ratio of 1:1.
[0015] Preferably, the hindered phenolic antioxidant is one of antioxidant 1010, antioxidant 1076, antioxidant 264 and antioxidant 2246.
[0016] Preferably, the phosphite antioxidant is one of antioxidant 168, antioxidant 626 and antioxidant 9228.
[0017] Preferably, the hydrolysis stabilizer is carbodiimide.
[0018] The beneficial effects of this invention are: 1. This invention significantly improves the antistatic properties of the base film by introducing functional additives containing quaternary ammonium salt cationic groups, effectively preventing the adsorption of micro-dust due to tribostatics, avoiding quality problems such as contamination of the optical surface of the polarizer and black spots on the display, and simplifies the experimental operation compared with the traditional coating process. 2. The functional additive of this invention contains a rigid six-membered heterocycle of benzoxazine, which has an extremely high thermal decomposition temperature and can significantly improve the stability of the base film under thermal aging environment, making it suitable for harsh working conditions. In summary, the base film prepared by this invention overcomes the defects of existing BOPET base films in terms of antistatic properties and heat aging resistance, and improves the reliability and service life of polarizer release films in high-end display applications. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Example 1 Preparation of functional additives: S1. In a three-necked flask equipped with a mechanical stirrer and a reflux condenser, 40g of 4,4'-methylenediphenol, 27g of ethanolamine, and 150mL of toluene were added sequentially. The stirring was started, and the mixture was heated to 80°C. Then, 25.2g of paraformaldehyde (n=8-30) was added in four batches. After all the paraformaldehyde was added, the temperature was raised to 110°C, and the mixture was refluxed at this temperature for 4 hours. After the reaction was completed, the mixture was filtered, and the filtrate was evaporated under reduced pressure to remove some of the toluene. The filtrate was then purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate 4:1, volume ratio). The mixture was then evaporated to obtain intermediate product A. S2. In a four-necked flask equipped with a mechanical stirrer, a constant-pressure dropping funnel, and a reflux condenser, 37.1 g of intermediate product A and 120 mL of acetonitrile were added sequentially. Stirring was started, and the flask was placed in an ice-water bath (0-5℃) for cooling. Using a constant-pressure dropping funnel, 15.8 g of iodomethane was slowly added dropwise to the flask. After the addition was complete, the ice-water bath was removed, and the reaction system was slowly heated to 40℃. At this temperature, the reaction was refluxed for 6 hours. After the reaction was completed, the iodomethane and some acetonitrile were removed by rotary evaporation under reduced pressure. The product was then purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate 4:1, volume ratio). Rotary evaporation was performed to obtain intermediate product B. S3. In a four-necked flask equipped with a mechanical stirrer, reflux condenser, thermometer, and pressure reducing port, add 83g of terephthalic acid, 43.4g of ethylene glycol, 35g of polyethylene glycol (PEG1000), 15.2g of intermediate product B, and 0.3g of antimony glycol. Heat to 180℃, maintain the system pressure at -0.02MPa, and mechanically stir for 3 hours to complete the esterification reaction. After esterification, slowly introduce nitrogen into the flask to replace the air for 10 minutes, then increase the vacuum to -0.098MPa and heat to 210℃. Under these conditions, continue stirring and polycondensation for 6 hours until polycondensation is complete. Stop heating, release the vacuum, cool and solidify, then boil and wash twice with an ethanol / water mixture, and vacuum dry to obtain the functional additive.
[0021] A method for preparing a BOPET base film for use as a release film for polarizers includes the following steps: A1. 70 PET slices (optical film grade high purity PET slices, grade FG600) were pre-crystallized and vacuum dried (drying temperature was 140℃, time was 2h) to obtain pre-treated PET slices; A2. Add the pretreated PET chips, 8 parts of functional additives, 0.3 parts of composite antioxidant (antioxidant 1010 and antioxidant 168 are compounded in a mass ratio of 1:1) and 0.4 parts of carbodiimide into a vented twin-screw extruder (extrusion temperature range of 265-275℃), and melt the raw materials to form a melt. A3. After the melt is extruded through the die, it is tightly bonded to the quenching roller (22℃) by a high-voltage electrostatic bonding system, and rapidly cooled and shaped to form an amorphous casting (1000μm thick). A4. The cast sheet is fed into the longitudinal stretching unit and preheated to 72°C via gradient (combined with infrared auxiliary heating). The longitudinal stretching is achieved by the difference in roller speed (stretching ratio of 3.0 times) to obtain the film. A5. The film is smoothly held by the chain clamp and put into the tenter oven (which contains three functional areas: preheating, stretching and heat setting). The film is preheated (100℃) and stretched laterally (stretching ratio of 3.5 times) in sequence to obtain the stretched film. A6. The stretched film is placed in a high-temperature setting zone at 185℃ and kept at that temperature for 5 seconds to complete the crystallization setting. Then, a slow gradient cooling annealing is used to fully release the residual internal stress and obtain the set film. A7. After the film has been shaped, it is cooled gently to room temperature, corona-treated, wound up, and slit to obtain the BOPET base film for polarizer release film.
[0022] Example 2 Preparation of functional additives: S1. In a three-necked flask equipped with a mechanical stirrer and a reflux condenser, 40 g of 4,4'-methylenediphenol, 28.2 g of ethanolamine, and 150 mL of toluene were added sequentially. The stirring was started, and the mixture was heated to 85 °C. Then, 25.2 g of paraformaldehyde (n=8-30) was added in 5 batches. After all the addition was completed, the temperature was raised to 115 °C, and the mixture was refluxed at this temperature for 5 h. After the reaction was completed, the mixture was filtered, and the filtrate was evaporated under reduced pressure to remove some of the toluene. The filtrate was then purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate 4:1, volume ratio). The mixture was then evaporated to obtain intermediate product A. S2. In a four-necked flask equipped with a mechanical stirrer, a constant-pressure dropping funnel, and a reflux condenser, 37.1 g of intermediate product A and 120 mL of acetonitrile were added sequentially. Stirring was started, and the flask was placed in an ice-water bath (0-5℃) for cooling. Using a constant-pressure dropping funnel, 16.2 g of iodomethane was slowly added dropwise to the flask. After the addition was complete, the ice-water bath was removed, and the reaction system was slowly heated to 45℃. At this temperature, the reaction was refluxed for 8 hours. After the reaction was completed, the iodomethane and some acetonitrile were removed by rotary evaporation under reduced pressure. The product was then purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate 4:1, volume ratio). Rotary evaporation was performed to obtain intermediate product B. S3. In a four-necked flask equipped with a mechanical stirrer, reflux condenser, thermometer, and pressure reducing port, add 83g of terephthalic acid, 43.4g of ethylene glycol, 35g of polyethylene glycol (PEG1000), 16.1g of intermediate product B, and 0.3g of antimony glycol. Heat to 185℃, maintain the system pressure at -0.02MPa, and mechanically stir for 4 hours to complete the esterification reaction. After esterification, slowly introduce nitrogen into the flask to replace the air for 20 minutes, then increase the vacuum to -0.098MPa and heat to 215℃. Under these conditions, continue stirring and polycondensation for 8 hours until polycondensation is complete. Stop heating, release the vacuum, cool and solidify, then boil and wash twice with an ethanol / water mixture, and vacuum dry to obtain the functional additive.
[0023] A method for preparing a BOPET base film for use as a release film for polarizers includes the following steps: A1. 75 PET slices (optical film grade high purity PET slices, grade FG600) were pre-crystallized and vacuum dried (drying temperature was 150℃, time was 3h) to obtain pre-treated PET slices. A2. Add the pretreated PET chips, 11.5 parts of functional additives, 0.45 parts of composite antioxidant (antioxidant 1010 and antioxidant 168 are compounded in a mass ratio of 1:1) and 0.65 parts of carbodiimide into a vented twin-screw extruder (extrusion temperature range of 265-275℃), and melt the raw materials to form a melt. A3. After the melt is extruded through the die, it is tightly bonded to the quenching roller (30℃) by a high-voltage electrostatic bonding system, and rapidly cooled and shaped to form an amorphous casting (1000μm thick). A4. The cast sheet is fed into the longitudinal stretching unit and preheated to 96°C via gradient (combined with infrared auxiliary heating). The longitudinal stretching is achieved by the difference in roller speed (stretching ratio of 3.0 times) to obtain the film. A5. The film is smoothly held by the chain clamp and put into the tenter oven (which contains three functional areas: preheating, stretching and heat setting). The film is preheated (150℃) and stretched laterally (stretching ratio of 3.5 times) in sequence to obtain the stretched film. A6. The stretched film is placed in a high-temperature setting zone at 238℃ and kept at that temperature for 15 seconds to complete the crystallization setting. Then, a slow gradient cooling annealing is used to fully release the residual internal stress and obtain the set film. A7. After the film has been shaped, it is cooled gently to room temperature, corona-treated, wound up, and slit to obtain the BOPET base film for polarizer release film.
[0024] Example 3 The only difference between this embodiment and Embodiment 1 is that, in this embodiment, a method for preparing a BOPET base film for a polarizer release film includes the following steps: A method for preparing a BOPET base film for use as a release film for polarizers includes the following steps: A1. Pre-crystallize and vacuum dry 80 PET slices (optical film grade high purity PET slices, grade FG600) to obtain pre-treated PET slices. A2. Add the pretreated PET chips, 15 parts of functional additives, 0.6 parts of composite antioxidant (antioxidant 1010 and antioxidant 168 are compounded in a mass ratio of 1:1) and 0.9 parts of carbodiimide into a vented twin-screw extruder (extrusion temperature range of 265-275℃), and melt the raw materials to form a melt. A3. After the melt is extruded through the die, it is tightly bonded to the quenching roller (30℃) by a high-voltage electrostatic bonding system, and rapidly cooled and shaped to form an amorphous casting (1000μm thick). A4. The cast sheet is fed into the longitudinal stretching unit and preheated to 96°C via gradient (combined with infrared auxiliary heating). The longitudinal stretching is achieved by the difference in roller speed (stretching ratio of 3.0 times) to obtain the film. A5. The film is smoothly held by the chain clamp and put into the tenter oven (which contains three functional areas: preheating, stretching and heat setting). The film is preheated (100℃) and stretched laterally (stretching ratio of 3.5 times) in sequence to obtain the stretched film. A6. The stretched film is placed in a high-temperature setting zone at 238℃ and kept at that temperature for 15 seconds to complete the crystallization setting. Then, a slow gradient cooling annealing is used to fully release the residual internal stress and obtain the set film. A7. After the film has been shaped, it is cooled gently to room temperature, corona-treated, wound up, and slit to obtain the BOPET base film for polarizer release film.
[0025] Comparative Example 1 The difference between this comparative example and Example 1 is that, in the process of preparing the functional additives, only step S3 (intermediate product B was not prepared, and the product was a common polyether ester antistatic agent) was used to prepare the base film.
[0026] Comparative Example 2 The difference between this comparative example and Example 1 is that a commercially available antistatic agent (manufacturer: Enze Chemical Antistatic Agent, model: Z101) was used to replace the functional additive in the raw materials to prepare the base film.
[0027] The following performance tests were performed on Examples 1, 2, and 3, and Comparative Examples 1 and 2: The surface resistivity of the sample was determined according to GB / T 31838.3-2019 standard (low humidity 30% RH). The transmittance and haze of the samples were determined according to GB / T 2410-2008 standard; then the samples were heat-aged at 120℃ for 200h in a forced-air drying oven, and the transmittance of the samples was determined again. Using a birefringence optical axis measuring instrument, five points were evenly distributed along the test width (lateral direction). A 20mm × 20mm sample was cut and placed in an orthogonally polarized optical path (wavelength 589nm). The stage was rotated to the extinction position, and the angle between the molecular chain main chain orientation direction and the mechanical longitudinal direction (MD direction) of the thin film was recorded. A Senarmont compensator was used for precise compensation, the compensation angle was read, and the absolute value of the angle was calculated. The heat shrinkage rate of the sample after heat aging at 150℃ for 30 min was determined according to GB / T 12027-2004 standard. The measurement results are shown in Table 1: Table 1
[0028] As can be seen from the measurement results in Table 1, the base film prepared by the present invention, while ensuring optical performance, has higher antistatic and heat aging resistance than the comparative example. Therefore, the present invention has important application value in the field of polyester film technology.
[0029] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A BOPET base film for use as a release film for polarizers, comprising the following raw materials in parts by weight: 70-80 parts PET chips, 8-15 parts functional additives, 0.3-0.6 parts composite antioxidants and 0.4-0.9 parts hydrolytic stabilizers.
2. The BOPET base film for polarizer release film according to claim 1, characterized in that, The functional additive is prepared through the following steps: S1. In a flask, add 4,4'-methylenediphenol, ethanolamine and toluene, start stirring and heat to 80-85℃, then add paraformaldehyde, raise the temperature to 110-115℃, reflux for 4-5 hours, the reaction is complete, and intermediate product A is obtained. S2. Add intermediate product A and acetonitrile to the flask, start stirring, and place the flask in an ice-water bath to cool. Slowly add iodomethane dropwise to the flask. After the addition is complete, heat the reaction system to 40-45℃ and reflux for 6-8 hours. The reaction is complete, and intermediate product B is obtained. S3. In a flask, terephthalic acid, ethylene glycol, polyethylene glycol, intermediate product B, and antimony glycol are added sequentially. The temperature is raised to 180-185℃, and the reaction is carried out under slight negative pressure for 3-4 hours to complete esterification. Nitrogen gas is then introduced into the flask to replace the air, and the vacuum degree is increased. Polycondensation is carried out at 210-215℃ for 6-8 hours. After the polycondensation is completed, the functional additive is obtained.
3. The BOPET base film for polarizer release film according to claim 2, characterized in that, In step S1, the ratio of 4,4'-methylenediphenol, ethanolamine, and paraformaldehyde is 20g:13.5-14.1g:12.6g.
4. The BOPET base film for polarizer release film according to claim 2, characterized in that, In step S2, the ratio of intermediate product A to iodomethane is 37.1 g: 15.8-16.2 g.
5. A BOPET base film for polarizer release film according to claim 2, characterized in that, In step S3, the ratio of terephthalic acid, ethylene glycol, polyethylene glycol and intermediate product B is 83g:43.4g:35g:15.2-16.1g.
6. The BOPET base film for polarizer release film according to claim 1, characterized in that, The composite antioxidant is a mixture of hindered phenolic antioxidants and phosphite antioxidants in a mass ratio of 1:
1.
7. A BOPET base film for polarizer release film according to claim 6, characterized in that, The hindered phenolic antioxidant is one of antioxidant 1010, antioxidant 1076, antioxidant 264 and antioxidant 2246.
8. A BOPET base film for polarizer release film according to claim 6, characterized in that, The phosphite antioxidant is one of antioxidant 168, antioxidant 626, and antioxidant 9228.
9. The BOPET base film for polarizer release film according to claim 1, characterized in that, The hydrolysis stabilizer is carbodiimide.